Assessing the impact of seed priming by nanomaterials on stevia germination and biochemical attributes under drought stress - Safaeipour, Mahla; Kalat, Mohsen Nabavi; Shahverdi, Mehdi Aghighi (Fundamental and Applied Agriculture, 2023)
Seed priming with nanocompounds can potentially enhance seed germina- tion and tolerance to environmental stress. The study examined the effects of drought stress induced by PEG-6000 at various levels (0, −0.3, −0.6, and −0.9 MPa) and seed priming with different nano-compounds (zinc oxide, titanium oxide, or silicon) on the germination, growth, and biochemical and physio- logical characteristics of stevia. The results showed that drought stress had a negative impact on most seed germination and growth parameters, while seed priming with zinc oxide nanoparticles had the highest positive impact. Different seed priming treatments produced varying outcomes. Drought stress and seed priming also significantly affected total chlorophyll content, chlorophyll a and b, and antioxidant enzyme activity (catalase and peroxidase). Under severe drought stress, all the three seed priming combinations significantly increased total chlorophyll content. Increasing the concentration of PEG-6000 in the seedling growth medium increased catalase activity. Non-primed seeds and seeds primed with zinc oxide under severe drought stress had the highest peroxidase enzyme activity. The Pearson correlation analysis revealed significant correlations among the measured traits. Lastly, the stepwise regression analysis identified catalase and peroxidase activities as the most influential traits related to stevia seed germination percentage. Seed priming with zinc oxide nanoparticles can enhance stevia seed germina- tion and growth, particularly under drought stress, by adjusting antioxidant enzyme activity and increasing photosynthetic pigment content. Moreover, as a practical outcome, the utilization of priming can serve as an applicable approach in the production of seedlings for this plant.